Realising the non-Hermitian skin effect with a nonlinear circuit - Lo, Hsuan (Nanyang Technological University, 2024)
The non-Hermitian skin effect (NHSE) is an intriguing phenomenon that occurs in certain lattices described by a non-Hermitian Hamiltonian, with eigenstates accumulating at one end of the lattice under open boundaries. The conventional method for generating the NHSE involves asymmetric hopping between lattice sites, which has proven difficult to implement in many metamaterial platforms. In this study, we present a novel approach for realizing the NHSE in a symmetrical RLC transmission line. We demonstrate NHSE through engineered hoppings of Bogoliubov quasiparticles by applying the Bogoliubov-de-Gennes (BdG) transformation to the equivalent GrossPitaevskii (GP) equation for the nonlinear circuit. Our findings indicate the presence of a phase transition in the free energy and topological winding number of the equivalent GP equation, emphasizing the importance of driving voltage in the manifestation of NHSE. The study also proposes a comprehensive experimental verification setup, which includes a printed circuit board designed specifically for observing NHSE in nonlinear circuits.